2015
DOI: 10.1680/geot.sip.15.p.009
|View full text |Cite
|
Sign up to set email alerts
|

A case study on the seismic performance of earth dams

Abstract: The seismic nonlinear behaviour of earth dams is investigated by using a well-documented case study and employing advanced static and dynamic coupled-consolidation finite element analysis. The static part of the analysis considers the layered construction, reservoir impoundment and consolidation, whereas the dynamic part considers the response of the dam to two earthquakes of different magnitude, duration and frequency content. The results of the analysis are compared with the recorded response of the dam and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…As far as dynamic response is concerned, deformation properties are of interest and govern the natural periods and modes of vibration of the dam. More information about the material properties may be found by Pelecanos (2013) and Pelecanos et al (2015) and issues related to its vibration in the narrow canyon by Pelecanos et al (2019a). In the first part, the dam is considered to be built on rigid bedrock foundation and therefore the dam foundation layer is ignored.…”
Section: Case Study: La Villita Dam Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…As far as dynamic response is concerned, deformation properties are of interest and govern the natural periods and modes of vibration of the dam. More information about the material properties may be found by Pelecanos (2013) and Pelecanos et al (2015) and issues related to its vibration in the narrow canyon by Pelecanos et al (2019a). In the first part, the dam is considered to be built on rigid bedrock foundation and therefore the dam foundation layer is ignored.…”
Section: Case Study: La Villita Dam Mexicomentioning
confidence: 99%
“…The dynamic FE method proved to be a superior technique and therefore dominated the seismic dam analysis activities. Indeed, a plethora of pseudo-static (Kontoe et al, 2013) and dynamic FE studies followed and nonlinear FE analysis (Elia et al, 2011;Pelecanos et al, 2012a;2012b;2013b;2015;2018a;Han et al, 2016, Shire et al, 2013 is now considered the current state-of-the-art. Nevertheless, dam-reservoir interaction effects are considered insignificant for earth dams (Pelecanos et al, 2013a;2017;2019b).…”
Section: Dynamic Analysis Of Earth Damsmentioning
confidence: 99%
“…Earthquake seismicity can cause additional loads on dam and increasing the pore water pressure also the field investigation showed that the slope instability is the main effect of earthquake and cause failure of the dam [3]. Also, an earthquake can cause structural failure and excitation of an embankment dam, which can result in the failure of the whole dam.…”
Section: Introductionmentioning
confidence: 99%